Metabolic and Behavioral Effects of Serotonergic Antidepressants in Rats Exposed to Swim Endurance Stress - Mehnaz Gitay; Samina Bano (Journal of Basic & Applied Sciences, 2013)
Metabolic syndrome (MS) is a collection of risk factors for coronary artery disease and type 2 diabetes. Prevalence of the MS in patients with depression is high and use of antidepressants also exert variable effects on constituent elements of the MS. Metabolic and behavioral effects of chronic serotonergic antidepressants treatment in rats subjected to swim endurance test (SET) were investigated. The Albino Wistar rats were divided into 2 groups vehicle (n=12) and drug (n=12). Each group was further divided into unstressed and stressed. Tianeptine (20 mg/kg), and sertraline (30 mg/kg), was administered orally for 28 days. Results showed that tianeptine and sertraline treatment correspondingly increase rat swimming time in SET. Swim stress raised circulating glucose, non-esterified free fatty acids (NEFFA), cholesterol, high density lipoprotein (HDL), low density lipoprotein (LDL) and corticosterone levels with no effects on triglycerides (TGs). Drug alone administration showed that serum glucose levels were decreased by sertraline but not by tianeptine. Lipid levels were raised by both the drugs without effecting TGs. When drug treated stressed group was compared with the stressed controls, showed that tianeptine increases total cholesterol and LDL whereas TGs were decreased with no change on glucose levels. However sertraline treatment decreased the circulating glucose levels while the lipid profile remained unchanged. Corticosterone levels were increased by both the drugs. In conclusion, both the drugs may contribute potentially to the development of MS.It is suggested that antidepressant therapy should include routine surveillance for clinical and/or biochemical evidence suggestive of the metabolic syndrome.